2021
DOI: 10.3390/heritage4040195
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Geoheritage Values: Implementation and Thematic Analysis Evaluation of a Synchronous Online Educational Approach

Abstract: The purpose of this article is to present the results of an environmental education program on “Storm-Tossed Sea Rocks in Pelion Seaside” designed for junior high school students and implemented as a synchronous online educational approach and main and with a main goal to empower students to the values of geoheritage. In order to examine the effectiveness of the program and in particular the achievement of the objectives that encourage the development of values, the research question was identified as to wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…This orientation in the development of perceptions and values in students showed teachers that such a diagnostic assessment technique should be followed which can deepen students' perceptions and knowledge and provide the necessary information to teachers to shape and properly implement the program in order to promote the empowerment of values in students. The latter instructed teachers to follow a similar assessment technique and process to that of Georgousis, Savelidi, Savelides, Holokolos and Drinia (2021) [50,71].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This orientation in the development of perceptions and values in students showed teachers that such a diagnostic assessment technique should be followed which can deepen students' perceptions and knowledge and provide the necessary information to teachers to shape and properly implement the program in order to promote the empowerment of values in students. The latter instructed teachers to follow a similar assessment technique and process to that of Georgousis, Savelidi, Savelides, Holokolos and Drinia (2021) [50,71].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study, one which investigated the understanding of geocultural heritage and the relative values of lower secondary school students (gymnasium) and university students, found that in contrast to the aesthetic value perceived by the participants and the importance they attach to cultural, anthropocentric, utilitarian and economic values, participants understand geological value to a moderate degree, and ecological, ecocentric and intrinsic values to a fairly low degree [47]. This is why, in the Greek school reality, the design and implementation of geoenvironmental education programs for lower secondary school (gymnasium) students is promising in the aims of empowering their geocultural values [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Data was collected from academic activities (2020–2022), which consist of the Development and Promotion of Science and Technology Talents (DPST) program mefrom the Kaennakhon Witthayalai School (10 persons), Earth Science Olympiad (ESO) Camp of Northeastern Center of Thailand (approximately 100 persons), Special Project of Bachelor Students (2 persons), Independent Study of Master Student (1 person), Preparatory Camp for Developing Junior Geologist of Department of Geotechnology (approximately 200 persons), and a virtual field trip, the Geoexplosive camp 2022 (online) for high school students from all over Thailand (30 persons). These activities were set a particular teaching method that was cognitively, educationally, and emotionally beneficial to students similar to geoeducation in Greece ( Georgousis et al., 2021 ) and Portugal ( Henriques et al., 2022 ). Therefore, the need to strengthen sustainable geoeducation issues related to environmental education, geodiversity, and geocultural heritage is justified.…”
Section: Resultsmentioning
confidence: 99%
“…In the qualitative investigation, the thematic evaluation technique was designated as the predominant mode of assessment, as observed in numerous instances [78][79][80]. This approach involves the systematic grouping, exploration, and systematic categorization of themes within the data.…”
Section: Methodsmentioning
confidence: 99%